Relationship between Organizational Justice Perception and Engagement in Deviant Workplace Behavior - Syaebani, Muhammad Irfan; Sobri, Riani Rachmawati (UI Scholars Hub, 2011)
Deviant workplace behavior is not something unusual and is prevalent in organizational dynamics. It is found in all types of organizations and in all levels of positions. This deviance is costly not only in financial, but also in social and psychological terms. This research aims to reveal whether there is any association between organizational justice perception and engagement in deviant workplace behavior since so many scholars argue that organizational injustice can serve as one of the causes to workplace deviance. Three forms of organizational justice are used in this research; they are: distributive, procedural, and interactional justice. Additionally, two dimensions are used to classify deviant workplace behavior, which are severity and target. Putting these two dimensions into low-high continuum, it helps to develop a typology of deviant workplace behavior into four classifications: production, political, property, and personal aggression. Result findings show us that organizational justice perception play important role in the occurrence of deviant workplace behavior. However, it is not the sole predictor since only one deviant workplace behavior (out of twelve) which correlates significantly with one form of organizational justice.